Exploring Autodidacticism in English Language Learning through the Power of Music on Ahmad Dahlan University - Abbas, Azwar; Amaliawati, Shafira; Aulia, Nila; Agustiningrum, Tessana (Global Synthesis in Education Journal, 2023)
Teaching ability is one of the components needed in achieving students’ competency targets. In this case, PPG program students need to master an effective teaching skill. In this study, the researchers aimed to examine the impact and experience of the Pres-service PPG program in developing teacher professionalism. The researchers provided three participants of the 2022/2023 Pre-service PPG program. This study used qualitative descriptive design and the interview technique was implemented to obtain the data. The results of this study indicate that the participants gave a positive response to the pre-service PPG program. This is shown from the results of the interviews that the program was very useful in improving teaching skills an the students  also got several benefits during the period of PPG program.